Elternwerden zwischen »Babyfernsehen« und medizinischer Überwachung: Eine Ethnografie pränataler Ultraschalluntersuchungen - Sänger, Eva (transcript, 2020)
Prenatal diagnostics as a family event? On the problematic re-functioning of imaging examinations by expectant parents.